Strength, Environmental Impact and Cost Assessment of Alkali-Activated Concrete with Pre-treated Coarse Recycled Aggregates - MD Ikramullah Khan; V. Vinayaka Ram; Vipulkumar Ishvarbhai Patel (International Journal of Concrete Structures and Materials)
Abstract Alkali-activated concrete (AAC) has been extensively developed to reduce the environmental impact caused by ordinary Portland cement (OPC), when used in plain cement concrete (PCC). This study supports sustainable construction and a global effort to reduce environmental impact and implement eco-friendly AAC through the effective use of industrial wastes (such as ground-granulated blast furnace slag and fly ash). In this work, natural coarse aggregates (NCA) are gradually substituted with coarse recycled aggregates (CRAs) and pre-treated coarse recycled aggregates (PCRAs). AAC, with a characteristic compressive strength of 40 MPa, was designed, cast, cured and tested (such as ultrasonic pulse velocity, strength, embodied energy (EE), CO2 emission and cost analysis) of AAC and PCC incorporating various coarse aggregates were investigated and presented to establish the suitability. The results indicate that 100% CRAs in AAC achieved a compressive strength of 41.33 MPa, with a substantial reduction in EE consumption by 70% and a 62% reduction in CO2 emission when compared to PCC cast with 100% CRA. The analysis clearly indicates that the OPC in PCC remains the major contributor towards both EE and CO2 emission. On the contrary, the binding activators, used in AAC, contribute relatively lesser EE and CO2 emission. Analysis revealed that AAC is 1.8–2 times costlier than the comparable PCC mixtures. The AAC mixtures with 100% PCRAs achieved 90% of the strength of those specimens with 100% NCA. The use of PCRAs in place of NCAs has resulted in substantial cost reduction.